GC-MS and Cellular Toxicity Studies on Smokeless-Tobacco Show Alerting Cytotoxic effect on Human Gingiva and Lung Fibroblasts - M. Ahmed Mesaik; Asaad Khalid; Ashraf N. Abdalla; Shahnaz Sultana; Abdel-Rahman Youssef; Izzaddinn E. Ahmed; Yassin I. Mohammed; Hyder O. Mirghani; Zia ur Rehman; Hassan A. Alhazmi; Mohammed Al Bratty (Journal of Spectroscopy)
Smokeless tobacco (SLT) has been reported to have deleterious effects on the health of its users. This study aims to analyze the constituents of locally collected SLT sample extracts (S1–S11) from Tabuk region of Saudi Arabia using GC-MS and investigate their cytotoxic effect on human gingival fibroblasts (hGFs), normal human fibroblasts (MRC5), and two cancer cell lines (HT29 and HepG2) using MTT assay. GC-MS results showed that pyridine, 3-(1-methyl-1H-pyrrol-2-yl)-, tetracyclo[4.4.1.1(7,10).0(2,5)]dodec-3-en-11-ol, and cotinine were found in S1, while ethyl iso-allocholate was traced in S2. Compounds 9,12-octadecadienoic acid, ethyl ester, 7-methyl-Z-tetradecen-1-ol acetate, cis-10-heptadecenoic acid and octadecanoic acid, ethyl ester, and nicotine traces were found in S4, while compound 3,7,11,15-tetramethyl-2-hexadecen-1-ol, tetradecamethyl-hexasiloxane, and phytol in S5. Additionally, octadecamethyl cyclononasiloxane, oleic acid, and trimethylsilyl ester were found in S6 and S9, respectively. Interestingly, extracts S4, S10, and S6 were the most cytotoxic to the normal fibroblasts (hGF and MRC5, with low selectivity index: <1), compared with doxorubicin and with their effect on the cancerous cells (HT29 and HepG2). Various components detected in SLT samples were carcinogenic, including nicotine and its derivatives, hexadecanoic acid, 1,2-benzenedicarboxylic acid, and octadecanoic acid. The present study showed that the cytotoxic and possibly carcinogenic effects of the SLT samples on gingiva and lung cells are attributed to many compounds and not only nicotine derivatives, all of which could create health threats for SLT users and lead to various types of cancers, including oral, lung, colon, and liver cancers.